Patient Adherence to Follow-Up in Clinical Research: A Systematic Review of Measurements, Associated Factors and Intervention Strategies - Xiaohang Wu; Haotian Lin (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
Objectives: A patient's adherence to follow-up (AFU) plays a key role in the implementation of clinical research with respect to cost and validity. Most present studies focus exclusively on some specific steps during clinical research implementation, regardless of the synthetic action of patientsociety-medicine system. The objective of the study is to provide a comprehensive systematic review of the measurements, associated factors and intervention strategies of AFU across a broad spectrum. Methods: A search was performed for studies that reported AFU in English in Medline, EMBASE, PubMed or the Cochrane Library from January 1995 to February 2014. Given the huge variety in study design and multifold complexity, a qualitative systematic review instead of meta-analysis was performed for the measurements, associated factors and intervention strategies of AFU according to Cochrane methodology. Results: A total of 125 included studies identified six measurements of AFU according to different definitions and calculations; the majority of studies used follow-up rate, with calculation methods varying in numerators but with the same denominator. The factors associated with AFU were assigned to 5 major categories, of which "individual patient characteristics" and "research design and practice setting" were most studied, with respect to having the most subcategories (12) and most related studies (76/125) respectively. The most studied type of the 3 major interventions used to improve AFU was information system and interaction improvement (56/99). Conclusions: The number of published studies regarding the measurements, associated factors and intervention strategies of AFU is increasing, which contributes to improving the final quality of clinical research. Individual patient-centered information system and interaction improvement have been gaining most attention, and would be the most important direction of development to improve patient AFU. While, the function of multiaspect environment factors and research design enhancement remain to be noticed.